Quantitative MRI assessment of idiopathic temporal lobe epilepsy: comparative study between automated MR volumetry and proton MR spectroscopy over conventional measures - Radwa Abo El-Kasem; Mona G. Maghrabi; Hosam E. G. Elmalah; Reda Badry; Shimaa Farghaly (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background and objectives Idiopathic temporal lobe epilepsy is the most common cause of focal epilepsy in adults. Due to its significant propensity for medical refractory behavior, it is often regarded as requiring additional assessment and potentially even surgical intervention. MRI has shown a beneficial role in the localization and lateralization of seizure foci. The objective of this study was to ascertain the advantages of automated MR volumetry and MR spectroscopy over conventional MRI in lateralization and prognostic assessment of idiopathic temporal lobe epilepsy. Methods This case–control study was conducted on 33 TLE cases and 40 healthy age- and sex-matched individuals. Study patients were classified into right and left TLE groups based on lateralization by EEG. History-taking, clinical neurological examination, standard MRI, and MRS were performed for both patient and control groups. Additionally, the patient group was subjected to EEG and automated MR volumetry. Finally, a comparison between these different MRI techniques was done. Results Both automated MR volumetry and MRS achieved greater sensitivity and accuracy than conventional MRI in the lateralizing idiopathic TLE; however, MRS showed the highest sensitivity and diagnostic accuracy, reaching 100% and 87.9% in the right TLE group and 88.2% and 90.9% in the left one, respectively. No statistically significant difference was found between hippocampal signal intensity among controlled and uncontrolled patients, while there was a statistically significant higher percentage of unilateral reduced hippocampal volumes among uncontrolled patients (66.7%) compared to controlled patients (23.8%) with (p = 0.027). Also, a statistically significant difference between controlled and uncontrolled cases regarding calculated tNAA/(Cho + Cr) ratio was found (p = 0.032), with a substantial mild positive correlation between tCho/Cr ratio and illness duration (r = 0.374, p = 0.032). Conclusions Quantitative MRI assessment of idiopathic TLE using automated MR volumetry and MRS is more sensitive and accurate than qualitative conventional visual analysis, thus performing these techniques in combination with EEG and clinical data would certainly increase MRI sensitivity and improve its diagnostic accuracy.